2018
DOI: 10.1007/s00270-018-1889-0
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Stent-Graft Repair of Spontaneous Isolated Dissection of the Superior Mesenteric Artery

Abstract: For symptomatic spontaneous isolated dissection of SMA in patients without aneurysms rupture and bowel necrosis, endovascular treatment with covered stents may be a safe and effective treatment option with a good short-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
2
19
2
Order By: Relevance
“…We read with great interest the recent article by Wen et al [1]. The authors reported 12 consecutive patients who received endovascular treatment with a covered stent and declared that endovascular treatment should be performed in patients with a spontaneous dissection of the superior mesenteric artery (SMA) patients who are symptomatic, without aneurysms rupture or bowel necrosis.…”
mentioning
confidence: 78%
“…We read with great interest the recent article by Wen et al [1]. The authors reported 12 consecutive patients who received endovascular treatment with a covered stent and declared that endovascular treatment should be performed in patients with a spontaneous dissection of the superior mesenteric artery (SMA) patients who are symptomatic, without aneurysms rupture or bowel necrosis.…”
mentioning
confidence: 78%
“…6 Covered stents can be used to seal the entry point and dissecting aneurysm; bare stents cannot be used for this purpose. 14,15 However, covered stents are not usually recommended for patients with IMAD because these stents can cause the obliteration of multiple side branches of the mesenteric artery, which may worsen intestinal ischaemia or even lead to intestinal necrosis. 7,16 This obliteration of the side branches does not occur with the use of bare stents alone or stent assisted coiling, and so these techniques are widely used in the management of IMAD.…”
Section: Discussionmentioning
confidence: 99%
“…(6,24,28) Long-term complications included stent stenosis, stent occlusion, stent thrombosis. (6,7,24) Endothelial injury, neointimal hyperplasia, and chronic inflammation could be the causes. (29,30) However, the incidence was relatively low and only 2.1% of the endovascularly treated patients had a secondary intervention.…”
Section: Discussionmentioning
confidence: 99%